Strength Training and Kinematics Parameters of Gait in Healthy Female Elderly - Heydar Sadeghi; Fahimeh Naghi Nejad; Hamid Rajabi (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: This study was under taken to consider the effect of strength training on some kinematics parameters of gait (step length, cadence and speed walking). Methods & Materials: Twenty-four healthy elderly women (with average and standard deviation age of 61.53±2.84 years, height of 157.1±5.5 cm, weight of 69.13±7.6 kg and BMI 28.1±3.6 kg/m) participated in this study. The strength of lower limb assessed using leg press test. The subjects were randomly divided in to control and experimental group. Video camera, 3DMax, Premier and Photoshop soft ware’s were used to measure speed walking, cadence and step length before and after training program. The control group continued their daily activity, while experimental group were in eight weeks for strength training for lower limb and body stabilizer muscles. Within group differences using T-test for independent groups and between group differences were analyzed using by T-test for dependent group before and after training at significant level of 0.05. Results: The changes of speed walking and lower limb strength weren't significant in control group. While significant differences observed in step length and speed walking and lower limb strength in experimental group. In comparison between groups, except of cadence, step length, speed walking and lower limb strength showed significant increase in experimental group. Conclusion: The results confirmed the effectiveness of strength training and increasing lower limb and stabilizer muscles strength on step length and speed walking in healthy elder women.